Vitamin A - potential anticancer weapon - Popławska, Natalia Aleksandra; Śliz, Justyna; Skorupska, Marta; Czeczotka, Magdalena Joanna; Woźniak, Krzysztof (Journal of Education, Health and Sport, 2024)
Introduction: Vitamin A, one of the most popular vitamins that people usually associate with eye health or beautiful skin, also has many other functions and uses. Recently many scientists conducted studies to determine if vitamin A could be a new weapon against cancers. Aim of the study: The aim of the study was to discuss recent findings regarding the impact of Vitamin A and other retinoids on potential applications in anticancer therapy. Materials and methods: This review of studies is based on scientific articles available in PubMed and Google Scholar databases. The names of the cancers were juxtaposed with term "Vitamin A" and with term "Retinoids" to gather data regarding the effect of retinoids on cancer treatment and prevention. Results: After analyzing the gathered publications, it is possible to conclude that retinoids can have a positive impact on cancer treatment. Some of them can induce apoptosis of cancer cells and others can reduce their proliferation. Moreover, retinoids can also play an important role in preventing cancers, such as ovarian, breast, cervical, or skin cancer. The role of retinoids in the prevention of prostate cancer remains unclear due to conflicting research results. Conclusion: The studies have shown promising results which indicate a need for further research into anticancer mechanisms of retinoids. Specifically, more research is needed to explore the positive impact of retinoid use in treating cancer diseases. The significant potential of retinoids may make it possible to include them in clinical practice and develop an effective therapeutic strategy for cancer treatment based on them.